An Overview of Functional Magnetic Resonance Imaging Techniques for Organizational Research. (January 2019) - Loued-Khenissi, Leyla; Döll, Olivia; Preuschoff, Kerstin
Functional magnetic resonance imaging is a galvanizing tool for behavioral scientists. It provides a means by which to see what the brain does while a person thinks, acts, or perceives, without invasive procedures. In this, fMRI affords us a relatively easy manner by which to peek under the hood of behavior and into the brain. Characterizing behavior with a neural correlate allows us to support or discard theoretical assumptions about the brain and behavior, to identify markers for individual and group differences. The increasing popularity of fMRI is facilitated by the apparent ease of data acquisition and analysis. This comes at a price: low signal-to-noise ratios, limitations in experimental design, and the difficulty in correctly applying and interpreting statistical tests are just a few of the pitfalls that have brought into question the reliability and validity of published fMRI data. Here, we aim to provide a general overview of the method, with an emphasis on fMRI and its analysis. Our goal is to provide the novice user with a comprehensive framework to get started on designing an imaging experiment in humans.